DIFFERENT CONCEPTS OF STRICT LIABILITY: THE DRAFT COMMON FRAME OF REFERENCE AND THE PRINCIPLES OF EUROPEAN TORT LAW AS ROLE MODELS FOR SERBIAN LAW? - Sekulić, Miloš B. (Pravni zapisi, 2019)
Within the European Union, numerous development projects have been created with the aim of harmonizing the civil law. These projects, created as a result of the work of lawyers and research centres across Member States of the European Union, are part of the so-called "soft law" and may serve as role models for national legislators, including here the Serbian lawmaker, for regulating certain issues. Development projects touch upon practically all aspects of contemporary civil law, to a greater or lesser extent, and the emphasis in this paper is to analyse the strict liability for damage as an important form of liability for damage in the modern world, full of increased risks to people and their environment. The development projects taken as examples of how this form of liability can be regulated in different manners are the Draft Common Frame of Reference and the Principles of European Tort Law. The aim of this paper is to determine whether Serbian legislation on strict liability can be improved through the introduction of rules from these acts. Key words: Draft Common Frame of Reference, Principles of European Tort Law, Contracts and Torts Act, general case of strict liability, special cases of strict liability.